Tamnica između mora i neba - Bošnjak, Branimir (2008)
The life and literary work of Croatian poet Stojan Vučićević is a tragic example of the fate of Croatians in the second half of the twentieth century, and an exceptional example of poets who share this fate, a fate that is sanctioned in writing only by a Council of Europe Resolution condemning Communist crimes (Strasbourg, 25 January 2006), while we continue our silence. Vučićević was born in 1941 in the village of Turkovići in eastern Herzegovina. As an underage youth he was, for political reasons, incarcerated and taken to a concentration camp on the small island of Sveti Grgur where he was kept for a year and a half. And just as it did with the Russian writer Dostoyevsky, that event was pivotal in setting the tone of his literary creativity. His work possesses the experience of the mysticism of pain and bears the imprint of a master of the art. He was intensively engaged in literary work, translated and served at the post of editor of literary periodicals. His literary work encompasses five collections of poetry and the travelogue Podmornica (The Submarine). He passed away young, in 1989. As a legacy of life between two deaths the poet left a recently released selection of poems of his own choosing entitled Semafor (Stoplight). His tragic and unquenchable nature bears witness to a lasting place in Croatian poetry.
Summary ; resumen
Keywords: Vučićević, Stojan